E-Government Implementation to Support Digital Village in Indonesia: Evidence from Cianjur Village, Bogor Regency - Aniqotul Ummah; Siti Maryam; Danis Tri Saputra Wahidin (Jurnal Studi Sosial dan Politik, 2022)
The implementation of e-government is considered as one of the bureaucratic reforms in terms of improving local public services, in Indonesia itself we can trace starting from Presidential Instruction Number 6 of 2001 concerning Telecommunications, Media, and Informatics, until later Presidential Decree Number 20 of 2006 established the National Information and Communication Technology Council with the aim of accelerating the implementation of e-government. Although referring to the 2020 E-Government Development Index (EGDI) assessment survey issued by the United Nations every 2 years, it shows that Indonesia's position is ranked 88th, up from 107th in 2018, the digital divide and inequality of internet access in various regions are inevitable. Taking a case study of Cijantur Village, Rumpin District, Bogor Regency, in order to support digital village program, this study tries to see the extent of the effectiveness of the implementation of website-based E-Service by the local community. Using a qualitative approach with observation data and literature studies collecting data method, this study concluded that the failure of the implementation of website-based e-government in Cijantur village is influenced by many factors including, residents' knowledge about the use of websites, the orientation of e-government development has not targeted the aspect of utilizing digital economy, and the level of community needs, whereas villages that still lack access to digital tools. This research suggests that there must be attention by relevant officials, so that Cijantur village is no longer an isolated village and streghtening construction and infrastructure of Cijantur village and provide a strong internet network to support the progress of the community in the field of technology.